Kajian Peran E-Commerce terhadap Perluasan Akses Pasar Ekspor Kelapa Sawit Indonesia - Ernah, Ernah; Tauladani, Jastitia Arifania; Safitri, Khalisya Rahma; Bhakti, Anneke Lamarsha (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Palm oil is one of Indonesia’s key export commodities, contributing significantly to the national economy. However, the expansion of exports continues to face challenges such as limited distribution channels, restricted access to global markets, and a lack of transparency in the supply chain. Amid rapid advancements in digital technology, e-commerce has emerged as a potential solution to address these issues, particularly for downstream products such as crude palm oil (CPO). This study aims to analyze the role of e-commerce in supporting the export of Indonesian palm oil commodities to global markets. The research employs a qualitative-descriptive approach using literature review and secondary data analysis sourced from trade institutions and e-commerce platforms. Content analysis was used to examine relevant documents and data to identify patterns, opportunities, and constraints. The findings indicate that e-commerce contributes to accelerating product promotion, expanding international buyer networks, and improving logistics efficiency and transaction transparency in export activities. Nevertheless, several obstacles remain, including limited digital trade regulations, uneven digital infrastructure across regions, and low digital literacy among agribusiness MSMEs. This study concludes that e-commerce holds considerable potential to enhance the global reach of Indonesia's palm oil exports. Therefore, it is recommended that the government adopt supportive policies, strengthen the capacity of small and medium enterprises, and integrate digital logistics systems at the national level to fully harness the benefits of e-commerce in export development.